Samspel mellan amerikansk blomtrips, Frankliniella occidentalis, och kruk-gerbera, Gerbera jamesonii - Roth, Lena (2004)
Gerbera jamesonii is a plant with a large amount of pollen and various flower colours and a favourite host plant for Frankliniella occidentalis. The best growing temperature for gerbera is approximately 20°C. Frankliniella occidentalis or the Western Flower Thrips is a small insect that has become an important pest in greenhouse cultivation all over the world. The high temperatures in the greenhouse are favourable for F. occidentalis. The damages from this pest can be found in flower buds or in growing points. When thrips are piercing the cells and sucking out their contents, the cells are filled with air, which results in silvery spots on the infected plant parts. The leaves can be deformed as a result of the cells collapsing after the sucking. Later necrotic spots can appear and the injured plant part fades and becomes brown. Moreover on the leaves the insect's excreta can be seen as black spots. The damage on the plant is not visible until the damaged plant part (flower buds and leaves) starts to open, that is why it is important with preventive work. Continuous control of the plants is necessary in order to be able to apply an adequate control strategy before the Thrips population gets too large. Biological control is particularly hard to use because F. occidentalis develops very quickly while the reproduction of the natural enemies cannot keep up. Chemical control is also hard to use because Frankliniella occidentalis quickly can develop resistance. Frankliniella occidentalis and gerbera have the same temperature optimum and that makes temperature hard to use as a control mechanism for this pest. At low temperatures F. occidentalis develops more slowly and gerbera plants become smaller and vegetative. High temperatures up to 30ºC favours the Western Flower Thrips whereas the gerbera plant becomes high and elongated at high temperatures. Very high humidity is harmful to gerbera as well as to F. occidentalis. Gerbera can get fade disease and rots while thrips can get caught in the condense-water. The access to pollen is an important roll for the time of development of a Frankliniella population; increasing access results in a faster growth. A large amount of buds and young leaves is an asset for the pest as well as flowering plants. Preventative work including cleaning and control in the greenhouse with sticky traps and good hygiene is a step towards preventing and reducing infestations. More knowledge about the biological interaction between the host plant and the pest is needed to find new control strategies.